THE EFFECT OF AEROBIC EXERCISE ON BLOOD SUGAR LEVELS IN ADOLESCENTS AT RISK OF DIABETES MELLITUS - Purnama; Susy Puspasari (rifascholarpublisher.com, 2026)
Background: Indonesia ranks fifth in the number of people with diabetes. Diabetes cases in Indonesia reach hundreds of thousands, with the majority of sufferers aged over fifteen years. Cases of diabetes mellitus have risk factors that will increase the incidence of diabetes mellitus in 3-4 years later, especially in adolescence related to bad habits towards lifestyle, one of which is lack of physical activity. Some physical activities that are suitable for adolescents such as aerobic exercise that can reduce blood sugar levels. Purpose: This study aims to analyze the effect of aerobic exercise on blood sugar levels in adolescents at risk of diabetes mellitus. Methods: This study was Quasi experiment design with a pre-test and post-test two group design. The sample was 60 adolescents who were divided into intervention and control groups. Inclusion criteria were class VIII students, mild and moderate DM risk, and exclusion criteria were severe DM risk. Measurement of blood sugar levels was carried out before and after the intervention using a glucometer. For data analysis using Paired Sample T-Tests and ANCOVA. Results: The results showed a significant decrease in blood sugar levels in the intervention group p-value 0.00, while the control group p-value 0.77. Aerobic exercise has an effect on blood sugar levels with a p-value of 0.00. Conclusion: Aerobic exercise can reduce blood sugar levels while in adolescents at risk of diabetes mellitus. Health promotion programs in schools should integrate regular aerobic exercise sessions into the physical education curriculum, particularly targeting adolescents at risk of diabetes mellitus